Production of GMP-Compliant Clinical Amounts of Copper-61 Radiopharmaceuticals from Liquid Targets - Alexandra I. Fonseca; Vítor H. Alves; Sérgio J. C. do Carmo; Magda Silva; Ivanna Hrynchak; Francisco Alves; Amílcar Falcão; Antero J. Abrunhosa (MDPI AG, 2022)
PET imaging has gained significant momentum in the last few years, especially in the area of oncology, with an increasing focus on metal radioisotopes owing to their versatile chemistry and favourable physical properties. Copper-61 (t1/2 = 3.33 h, 61% β+, Emax = 1.216 MeV) provides unique advantages versus the current clinical standard (i.e., gallium-68) even though, until now, no clinical amounts of 61Cu-based radiopharmaceuticals, other than thiosemicarbazone-based molecules, have been produced. This study aimed to establish a routine production, using a standard medical cyclotron, for a series of widely used somatostatin analogues, currently labelled with gallium-68, that could benefit from the improved characteristics of copper-61. We describe two possible routes to produce the radiopharmaceutical precursor, either from natural zinc or enriched zinc-64 liquid targets and further synthesis of [61Cu]Cu-DOTA-NOC, [61Cu]Cu-DOTA-TOC and [61Cu]Cu-DOTA-TATE with a fully automated GMP-compliant process. The production from enriched targets leads to twice the amount of activity (3.28 ± 0.41 GBq vs. 1.84 ± 0.24 GBq at EOB) and higher radionuclidic purity (99.97% vs. 98.49% at EOB). Our results demonstrate, for the first time, that clinical doses of 61Cu-based radiopharmaceuticals can easily be obtained in centres with a typical biomedical cyclotron optimised to produce 18F-based radiopharmaceuticals.